Evaluation of Antibiotic Resistance and Virulence Genes among Clinical Isolates of Pseudomonas aeruginosa from Cancer Patients - Naveed Ahmed; Zeshan Ali; Mahpara Riaz; Basit Zeshan; Javed Iqbal Wattoo; Muhammad Naveed Aslam (Shahid Beheshti University of Medical Sciences, 2020)
Objectives: The objectives of this study were to evaluate P. Aeruginosa isolates from cancer patients for the phenotypic pattern of antibiotic resistance and to detect the gene responsible for virulence as well as antibiotic resistance. Methods: A total of 227 P. aeruginosa isolates were studied and 11 antibiotics were applied for susceptibility testing. PCR detection of the genes BIC, TEM, IMP, SPM, AIM, KPC, NDM, GIM, VIM, OXA, toxA and oprI was done. Finally, the carbapenem resistant isolates were tested for phenotypic identification of carbapenemase enzyme by Modified Hodge test. Results: The results showed that the isolates were resistant to imipenem (95%), cefipime (93%), meropenem (90%), polymixin B (71%), gentamicin (65%), ciprofloxacin (48%), ceftazidime (40%), levofloxacin (39%), amikacin (32%), tobramycin (28%) and tazobactum (24%). The PCR detection of the carbapenem resistant genes showed 51% isolates were positive for IMP, GIM and VIM, 38% for AIM and SPM, 30% for BIC, 20% for TEM and NDM, 17% for KPC and 15% for OXA. However, toxA and oprI genes were not detected. 154 carbapenem resistant isolates were found positive phenotypically for carbapenemase enzyme identification by Modified Hodge test. Conclusion: The co-existence of multiple drug-resistant bodies and virulent genes has important implications for the treatment of patients. This study provides information about treating drug-resistant P. Aeruginosa and the relationship of virulent genes with phenotypic resistance patterns.